Analisis Efektivitas Kebijakan Perlindungan Lahan Pertanian Pangan Berkelanjutan Terhadap Ketahanan Pangan di Daerah Kabupaten Pandeglang - Yosi Eka Octavianti; Nurikah Nurikah (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
The government has published a regulatory of act number 41 in 2009 on The Protection of Sustainable Food Agricultural Land (LP2B) as effort to protect perennial agricultural land. It’s hoped will halt the conversion of rice fields, especially with technical irrigation can sustain regional food security to the Nation. In administration, this law has obstacle process or covering space; planning determination and can be said not to run as it should, that a comprehensive evaluation of the performance is required.The method used in this study is empirical juridical based on qualitative data approaches that come from primary data through interviews and field research on agricultural services pandeglang county's for data could be analyzed and result of discussions in research.The study of the writing requires a regulation of LP2B region and an evaluation to see how its effectiveness is connected with the various regulations that have been drafted. The mandate in act number 41 in 2009 began when planning came to completion. The data inventory efforts in planning of setting up the zoning became necessary by the government especially the region government of pandeglang district through agricultural services as a technical executioners.